Pregunta
upstudy study bank question image url

Three consecutive terms of a geometric series are given in terms of a constant \( x \). \( U_{3}=(x+5), U_{4}=(4 x-1) \) and \( U_{5}=(2 x+3) \). Find the sum to infinity of the series. (Correct to four significant figures). Answer:

Ask by Franklin Page. in Ghana
Feb 15,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The sum to infinity of the series is approximately 6.075.

Solución

¡Inicia sesión para desbloquear respuestas gratis!

Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.

star-icon Descubrir

Respondido por UpStudy AI y revisado por un tutor profesional

Mind Expander

To find the sum to infinity of the geometric series given the terms \( U_{3}=(x+5) \), \( U_{4}=(4x-1) \), and \( U_{5}=(2x+3) \), we need to determine the value of \( x \) first, and then the common ratio \( r \) of the series. The general terms of a geometric series have the property that the ratio of successive terms is constant. Therefore, we can set up the equation: \[ \frac{U_{4}}{U_{3}} = \frac{U_{5}}{U_{4}} \] Substituting in our expressions for \( U_{3}, U_{4}, \) and \( U_{5} \): \[ \frac{4x - 1}{x + 5} = \frac{2x + 3}{4x - 1} \] Cross-multiplying gives us: \[ (4x - 1)^2 = (2x + 3)(x + 5) \] Expanding both sides: \[ 16x^2 - 8x + 1 = 2x^2 + 10x + 3x + 15 \] \[ 16x^2 - 8x + 1 = 2x^2 + 13x + 15 \] Rearranging the equation leads to: \[ 16x^2 - 2x^2 - 8x - 13x + 1 - 15 = 0 \] \[ 14x^2 - 21x - 14 = 0 \] Now we can simplify this by dividing all terms by 7: \[ 2x^2 - 3x - 2 = 0 \] Using the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): \[ x = \frac{3 \pm \sqrt{(-3)^2 - 4 \cdot 2 \cdot (-2)}}{2 \cdot 2} \] \[ = \frac{3 \pm \sqrt{9 + 16}}{4} = \frac{3 \pm 5}{4} \] Calculating the two solutions: 1. \( x = \frac{8}{4} = 2 \) 2. \( x = \frac{-2}{4} = -0.5 \) Now, we will substitute \( x = 2 \) back into the original equations: \[ U_{3} = 2 + 5 = 7, \quad U_{4} = 4(2) - 1 = 7, \quad U_{5} = 2(2) + 3 = 7 \] Thus, when \( x = 2 \), all three terms are 7. This confirms that it is a valid geometric series with a common ratio \( r = \frac{U_{4}}{U_{3}} = \frac{7}{7} = 1 \). The sum to infinity of a geometric series is given by the formula: \[ S = \frac{U_1}{1 - r} \] Since \( r = 1 \), we cannot find a finite sum because it diverges. Now let's check \( x = -0.5 \): \[ U_{3} = -0.5 + 5 = 4.5, \quad U_{4} = 4(-0.5) - 1 = -3, \quad U_{5} = 2(-0.5) + 3 = 2 \] The terms do not satisfy the geometric ratio condition, hence we discard it. Since with \( x = 2 \), we have \( r = 1 \), this implies the series diverges leading us to the conclusion: **Therefore, we cannot calculate the sum to infinity as it diverges.**

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad